2023
DOI: 10.3389/fnut.2023.1221685
|View full text |Cite
|
Sign up to set email alerts
|

A comparative absorption study of sucrosomial® orodispersible vitamin D3 supplementation vs. a reference chewable tablet and soft gel capsule vitamin D3 in improving circulatory 25(OH)D levels in healthy adults with vitamin D deficiency—Results from a prospective randomized clinical trial

Aasiya Bano,
Saida Abrar,
Elisa Brilli
et al.

Abstract: BackgroundVitamin D (Vit D) deficiency (VDD), associated with diverse health conditions, is commonly treated with Vit D3 supplements. However, the gastrointestinal (GI) absorption of Vit D3 in different formulations has not been well studied.ObjectiveWe aimed to compare the absorption of an innovative phospholipids-sucrester matrix biodelivery vehicle-based (sucrosomial®) orodispersible Vit D3 preparation against a reference chewable tablet and soft gel capsule (SGC) Vit D3 formulations in Vit D-deficient heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Bano et al compared three different Vitamin D 3 formulations administered at the same dose but using different treatment schedules in deficient adults. The authors concluded that a new orodispersible Vitamin D 3 formulation (sucrosomial ® ) achieved approximately twice the 25(OH)D levels compared to a chewable tablet administered weekly for 3 weeks at a dose of 200,000 IU (78.8 ± 7.1 vs. 36.1 ± 3.6 ng/mL) and outperformed softgel capsules administered every other week for 6 weeks (66.1 ± 5.1 vs. 38.2 ± 2.6 ng/mL) [ 47 ]. Radicioni et al found only slightly higher bioavailability of a new orally disintegrating film formulation of Vitamin D 3 when compared to standard oral Vitamin D 3 solution following a single dose of 25,000 IU, with Cmax values of 6.68 ± 2.03 vs. 6.61 ± 2.62 ng/mL [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bano et al compared three different Vitamin D 3 formulations administered at the same dose but using different treatment schedules in deficient adults. The authors concluded that a new orodispersible Vitamin D 3 formulation (sucrosomial ® ) achieved approximately twice the 25(OH)D levels compared to a chewable tablet administered weekly for 3 weeks at a dose of 200,000 IU (78.8 ± 7.1 vs. 36.1 ± 3.6 ng/mL) and outperformed softgel capsules administered every other week for 6 weeks (66.1 ± 5.1 vs. 38.2 ± 2.6 ng/mL) [ 47 ]. Radicioni et al found only slightly higher bioavailability of a new orally disintegrating film formulation of Vitamin D 3 when compared to standard oral Vitamin D 3 solution following a single dose of 25,000 IU, with Cmax values of 6.68 ± 2.03 vs. 6.61 ± 2.62 ng/mL [ 48 ].…”
Section: Discussionmentioning
confidence: 99%